Screw it, let's do it : lessons in life - Branson, Richard (London : Virgin, 2006)
Global entrepreneur Sir Richard Branson has built a business empire and made billions, yet is renowned for his approachability, ability to challenge and succeed against the odds. Screw It, Let's Do It reveals the lessons from life that have helped him through his business and personal life - such as, believe it can be done and that, if others disagree with you, try and try again until you achieve your goal; or that you must love what you do. These and other lessons, with examples of how he learned them and how he's used them, are included in this stirring and candid look at his lessons from an exceptional life, which will inspire you to make a difference in your own life
Introduction -- Just do it! -- Have fun! -- Be bold -- Challenge yourself -- Stand on your own feet -- Live the moment -- Value family and friends -- Have respect -- Do some good -- Epilogue -- Index
Keywords: Branson, Richard; Entrepreneurship; Success -- Psychological aspects